Clinical, laboratory and virological aspects in infectious mononucleosis of EBV- and HHV-6 etiology in children - N. S. Tian; I. V. Babachenko; O. V. Goleva; E. D. Orlova; N. S. Bezverkhaya; R. S. Kalinin; V. V. Tsay; E. V. Pinkovskaya; A. V. Krylov; A. V. Kusakin; Y. A. Eismont; A. L. Mukomolova; et al. (LLC "Diagnostics and Vaccines", 2023)
Purpose: To characterize clinical and laboratory features of infectious mononucleosis (IM) of EBV and HHV-6 etiology among children. Material and methods. A single-center prospective study was performed at Pediatric Research and Clinical Center for Infectious Diseases in 2021 - 2022, which included 84 patients with IM EBV (n = 40), HHV-6 (n = 11), EBV + HHV-6 (n = 33). Methods of laboratory diagnostics were clinical, biochemical blood tests, qualitative and quantitative PCR of blood (whole blood, plasma) to herpesvirus 4-6 types. Results. Patients with EBV IM were significantly older than children with HHV-6 IM and EBV + + HHV-6 IM (р ≤ 0,004). The main complaint of patients was fever (median 39,0°С, Q1-Q3 38,5-39,3°С). Nasal stuffiness (93%), tonsillitis (86%), peripheral cervical lymphadenopathy (100%) dominated among clinical manifestations in all groups. Splenomegaly was noted more rarely than hepatomegaly in children. There were no significant differences in the level of leukocytes among patients (р > 0,05). Increased values of lymphocytes, atypical mononuclear cells, hepatic cytolysis syndrome were characteristic of EBV-monoinfection (р ≤ 0,007). On the contrary, level of neutrophils was significantly higher in the HHV-6 IM group. Genotype HHV-6B was detected in 100% of cases. Assay of EBV viral load showed following: this indicator in plasma (р = 0,0008) and whole blood (р = 0,028) in EBV patients was significantly higher than among EBV + HHV-6 IM. A direct moderate correlation was found between viral loads in different human fluids (r = 0,413, р < 0,05). Conclusions. The results emphasize the importance of clinical and etiological diagnosis, including HHV-6 determination, for the well-timed registration of children with IM and their coverage with regular medical check-up.